Recent advances in sliding modes from control to intelligent mechatronics - Yu, Xing Huo; Efe, Mehmet Onder; Kaynak, Okyay (Springer International Publishing, 2015)
This volume is dedicated to Professor Okyay Kaynak to commemorate his life time impactful research and scholarly achievements and outstanding services to profession. The 21 invited chapters have been written by leading researchers who, in the past, have had association with Professor Kaynak as either his students and associates or colleagues and collaborators. The focal theme of the volume is the Sliding Modes covering a broad scope of topics from theoretical investigations to their significant applications from Control to Intelligent Mechatronics.